Waiting for Jeannot:: The (de) Construction of History in Brian Moore's No Other Life - Hicks, Patrick (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
In Brian Moore's No Other Life, Father Jeannot Cantave, after challenging the religious and social history of the fictitious Caribbean island of Ganae, abruptly disappears and leaves those around him waiting for his return, which strongly recalls Samuel Beckett's Waiting for Godot. In both texts, the primary concern is absence. In the case of No Other Life, the reassessment of history that occurs in the text subsequently allows the previously unexamined to become its focal point. Jeannot's departure (or absence) forces those around him to alter their viewpoints of history.